CD8+ lymphocyte decrease in HIV disease: association with anti-CD4+ but not with anti-CD8+ lymphocyte autoantibodies - Daniel, Volker; Süsal, Caner; Weimer, Rolf; Zipperle, Silvia; Kröpelin, Marianne; Zimmermann, Rainer Johannes; Huth-Kühne, Angela; Gerhard, Ingrid; Maier, Heinz; Opelz, Gerhard (Vox sanguinis, 1996)
HIV+ patients form autoantibodies against CD4+ and CD8+ lymphocytes. It was shown that anti-CD4+ lymphocyte autoantibodies are associated with the depletion of CD4+ cells. In the present study we analyzed the relationship of anti-CD4+ and anti-CDS+ autoantibodies with the CD8+ lymphocyte decrease commonly observed during HIV disease. IgM and IgG antibodies as well as complement fragments were determined on the surface of CD4+ and CD8+ lymphocytes using double fluorescence flow cytometry. Anti-CD8+ lymphocyte autoantibodies were found more often in HIV+ hemophilia patients (75/105 = 71%) than HIV- hemophilia patients (13/37 = 35%; p<0.0001), patients with pharyngeal carcinoma (20/44 = 45%; p = 0.002), habitual abortions (3/13 = 23%; p = 0.0009) or healthy individuals (93/223 = 42%; p< 0.0001). Anti-CD8+ antibodies, mostly of the IgM type, occurred significantly more frequently than anti-CD4+ antibodies in healthy controls (p< 0.0001), patients with pharyngeal carcinoma (p = 0.0001), or HIV- patients (p = 0.01). In HIV+ patients, however, anti-CD4+ autoantibodies were found more often than anti-CD8+ antibodies (85 vs 71%; p = 0.02). 70 of 104 (67%) HIV+ patients had autoantibodies on both CD4+ and CD8+ lymphocytes and the IgG/IgM/C3d autoantibody pattern was identical in 31 (44%) of the patients. Interestingly, peripheral blood CD8+ cell counts were significantly associated with anti-CD4+ (p = 0.01) but not with anti-CD8+ lymphocyte autoantibodies. It is hypothesized that the inhibition and depletion of CD4+ cells by anti-CD4+ autoantibodies is associated with a loss of regulatory functions that leads to a depletion of antiviral cytotoxic CD8+ lymphocytes.